Some Aspects of Business Operations of Serbian Economy in 2017 - Krstić, Saša; Fedajev, Aleksandra; Nikolić, Radmilo (Industrija, 2018)
After a period of stagnation, caused by the global economic crisis, the Serbian economy has been transformed into a growing economy with a satisfactory level of price and currency stability. In order to maintain this trend in the future and to ensure further acceleration of economic activity, it is necessary to identify the key problems faced by companies in every economic segment. In this sense, the aim of this paper is to identify the segments of the economy with the most favourable and the disadvantageous business economy, as well as the advantages and limitations of each segment individually. To perform this comparative analysis, the ratio analysis was applied in combination with PROMETHEE and the entropy method. Research results suggested that medium enterprises and those operating in the sector of information and communication and in the region of Vojvodina had the most favourable business economics, while the micro enterprises, those who operate in the construction sector and in the region of Kosovo and Metohija were in the worst economic and financial situation. On the basis of the obtained results, appropriate recommendations and guidelines for improvement of the business economics in the worst ranked segments of the economy have been defined.